Audit Capability Level Sipd Menggunakan Cobit 2019 Domain Align Plan And Organize Di Bappeda Kota Lhokseumawe - Angga Pratama; Ananda Faridhatul Ulva; Eza Pradanta Sitepu (Jurnal Tika, 2022)
The audit at the SIPD Bappeda of Lokseumawe City must be reviewed to see the efficiency and integrity of the company, for that it is necessary to audit the Capability level of the SIPD Bappeda of Lokseumawe City. The SIPD Capability Level audit was conducted with the aim of mapping the Capability Level of the I&T service and support process at the Lokseumawe City Bappeda. This SIPD Capability Level audit uses the Cobit 2019 Domain APO (Align, Plan and Organize) framework with a capability level calculation so that based on the results, recommendations for strategic goals will be found for the company for further development. Based on the current capability level obtained, the overall value is 2.527 and is at level 2 capability, namely Managed Process, meaning that the Lokseumawe City Bappeda has reached the implementation process and will later be determined according to the implementation process that has been implemented in this process in accordance with the Align, Plan and Domain processes. Organized at COBIT 2019. The 2019 COBIT model is also considered to be able to handle changes in governance and I&T Management in the company well.